Chirped pulse amplification in an all-normal-dispersion erbium-doped fiber amplifier. (10th February 2017) - Wang, Yiqin; Li, Lei; Zhao, Luming
Abstract: Chirped pulse amplification in an all-normal-dispersion erbium-doped fiber amplifier is presented. Wavelength dependent amplification is examined. It is found that gain dispersion limits the spectral profile of the amplified pulse. If the central wavelength of the seed pulse is far away from that of the gain profile of the amplifier, the gain profile partially shapes the spectrum of the amplified pulse while maintaining the characteristic steep spectral edge at one side. If the optical spectrum of the seed pulse is most covered by the gain profile, the characteristic steep spectral edges will be both maintained. The amplified pulse becomes deformed ultimately with increasing pump power, no matter whether the seed pulse is a transform-limited pulse or a chirped pulse.